Beheld - Flinn, Alex (Harperteen, a division of HarperCollins Publishers, 2017)
Kendra, a witch, uses a magic mirror to see her beloved James, whom she met in Salem, Massachusetts, but she loses track of him during World War II, and only finds a clue when she is in Miami, bringing a modern fairy tale couple together.